Pengaruh Fleksibilitas Waktu Kerja Terhadap Retensi Karyawan Melalui Kepuasan Kerja Pada Gojek Indonesia (International Forum of Researchers and Lecturers, 2025)
This study aims to examine the effect of work schedule flexibility on employee retention with job satisfaction as a mediating variable at Gojek Indonesia. The background of this research is based on the importance of retaining high-quality employees in the digital era, especially in technology companies that have fast-paced and highly adaptive work dynamics. This research employed a quantitative method with a causal design. Primary data were collected through questionnaires distributed to 150 Gojek Indonesia employees. The data were analyzed using simple linear regression and mediation tests to examine the proposed hypotheses. The results showed that work schedule flexibility has a positive and significant effect on employee retention. Furthermore, job satisfaction was proven to mediate the relationship between work schedule flexibility and employee retention. These findings indicate that the higher the work schedule flexibility provided by the company, the higher the job satisfaction, which in turn increases employee retention. Therefore, it is suggested that companies optimize their work schedule flexibility policies to improve employee satisfaction and loyalty.